Channel utilization of a half duplex ARQ protocol for packet radio channels. - Abaya, Efren F. (Philippine Engineering Journal)
ARQ is a common error control method for terrestrial data transmission. The different types of ARQ are reviewed, and channel utilization characteristics are summarized. A half duplex go back N ARQ method is presented as a model for the AX.25 ARQ protocol used in packet radio and an equation for channel utilization is derived and analyzed.